Exploratory and correlational study of cyberviolence in female college couples - Villalobos-Raygoza, Ariadna (2024)
Cyberviolence in dating is a social and public health problem, which is why the scientific community has increased its study, although the majority has focused on the heterosexual and cisgender population. Due to this, the objective of this research is to identify risk factors for cyberviolence in dating made up of women. This work made use of the Cyber ​​​​Dating Abuse Questionnaire, the Gender Role Attitudes Scale and an ad hoc questionnaire. about the practice of sexting; Therefore, it was carried out from the positivist paradigm with a quantitative approach to obtain the reliability and normality analyses, the main central tendencies, the distribution of frequencies per item and the correlations between the dimensions of the instruments used. Among the main findings was the low frequency of control behaviors and direct aggression online and a significant association of these with sexting and beliefs about the myths of romantic love. Likewise, the need to continue increasing research focused on sexual minorities for the development of specialized prevention and intervention programs in this community is highlighted.